Outcome of patients with local recurrent gynecologic malignancies after resection combined with intraoperative electron radiation therapy (IOERT) - Arians, Nathalie; Förster, Robert; Rom, Joachim; Uhl, Matthias; Röder, Falk; Debus, Jürgen; Lindel, Katja (Radiation oncology, 2016)
Treatment of recurrent gynecologic cancer is a challenging issue. Aim of the study was to investigate clinical features and outcomes of patients with recurrent gynecologic malignancies who underwent resection including IOERT (intraoperative electron radiation therapy) with regard to clinical outcome and potential predictive factors or subgroups that benefit most from this radical treatment regime.